2006
DOI: 10.1096/fj.06-6818com
|View full text |Cite
|
Sign up to set email alerts
|

TheTrypanosoma bruceicAMP phosphodiesterases TbrPDEBl and TbrPDEB2: flagellar enzymes that are essential for parasite virulence

Abstract: Cyclic nucleotide specific phosphodiesterases (PDEs) are pivotal regulators of cellular signaling. They are also important drug targets. Besides catalytic activity and substrate specificity, their subcellular localization and interaction with other cell components are also functionally important. In contrast to the mammalian PDEs, the significance of PDEs in protozoal pathogens remains mostly unknown. The genome of Trypanosoma brucei, the causative agent of human sleeping sickness, codes for five different PDE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
197
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 136 publications
(210 citation statements)
references
References 53 publications
13
197
0
Order By: Relevance
“…There is precedence for flagellar adenylate kinases as the central pair component cpc1 of C. reinhardtii contains an adenylate kinase domain (Zhang and Mitchell, 2004). Two additional PFR-associated proteins involved in nucleotide metabolism, TbrPDEB1 and TbrPDEB2, were recently identified (Zoraghi and Seebeck, 2002;Oberholzer et al, 2007). These cAMP phosphodiesterases localize to the flagellum, though the majority of TbrPDEB2 localizes to punctuate spots in the cytoplasm (Oberholzer et al, 2007).…”
Section: Paraflagellar Rodmentioning
confidence: 99%
See 3 more Smart Citations
“…There is precedence for flagellar adenylate kinases as the central pair component cpc1 of C. reinhardtii contains an adenylate kinase domain (Zhang and Mitchell, 2004). Two additional PFR-associated proteins involved in nucleotide metabolism, TbrPDEB1 and TbrPDEB2, were recently identified (Zoraghi and Seebeck, 2002;Oberholzer et al, 2007). These cAMP phosphodiesterases localize to the flagellum, though the majority of TbrPDEB2 localizes to punctuate spots in the cytoplasm (Oberholzer et al, 2007).…”
Section: Paraflagellar Rodmentioning
confidence: 99%
“…Two additional PFR-associated proteins involved in nucleotide metabolism, TbrPDEB1 and TbrPDEB2, were recently identified (Zoraghi and Seebeck, 2002;Oberholzer et al, 2007). These cAMP phosphodiesterases localize to the flagellum, though the majority of TbrPDEB2 localizes to punctuate spots in the cytoplasm (Oberholzer et al, 2007). Knockdown of flagellar ADKs or PDEBs did not impair growth of procyclic cells, but simultaneous ablation of PDEB1 and 2 was found to be lethal in bloodstream-form parasites (Zoraghi and Seebeck, 2002;Ginger et al, 2005;Oberholzer et al, 2007).…”
Section: Paraflagellar Rodmentioning
confidence: 99%
See 2 more Smart Citations
“…With regard to Trypanosoma brucei species, Zoraghi et al [15], Rascón et al [16], and Zoraghi et al [17] recently reported that T. brucei PDEs (TbPDE2 family: TbPDE2A, TbPDE2B and TbPDE2C) were found to be essential for bloodstream form trypanosome proliferation. Furthermore, Oberholzer et al, reported that TbPDE2B and TbPDE2C, as flagellar enzymes, were found to be essential for parasite virulence [18]. They also suggested that the TbPDE2 family might be considered as new molecular targets for chemotherapeutic antitrypanosomal drugs [15ϳ18].…”
Section: Discussionmentioning
confidence: 99%